"Wandering Capitals" and the Genesis of Addis Ababa (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2014)
Addis Ababa's current urban form in the old part of the city shows very irregular pattern filled with very dense, overcrowded or suffocated low-rise settlements. This urban area owes greatly to the original land colonization or inhabitation and culture. This inhabitation culture also goes further to the tradition of the "wandering capitals", which were non-permanent settlements or camps of kings. The paper tried to expound on the nature of these settlements and the shaping of the earliest urban form of Addis Ababa.